CT-based Abdominal Adipose Tissue Area Changes in Patients Undergoing Adrenalectomy Due to Cushing’s Syndrome and Non-functioning Adenomas - Gündoğdu, Elif; Emekli, Emre (Experimental and Clinical Endocrinology & Diabetes, 2021)
Background The majority of Cushing’s syndrome (CS) cases constitute patients with functional adrenal adenomas. In adrenal CS, visceral adipose tissue (VAT) area, VAT/subcutaneous adipose tissue (SAT), and VAT/total adipose tissue (TAT) ratios are expected to decrease in response to adrenalectomy, although no change is expected in non-functioning adrenal adenomas (NFA).Objective To evaluate the changes in VAT, SAT, TAT areas and VAT/SAT, VAT/TAT ratios using computed tomography (CT) in patients who underwent adrenalectomy due to adenomas.Methods Preoperative and postoperative CT of 32 patients (16 with CS and 16 with NFA) were retrospectively evaluated. The VAT, SAT, TAT areas were obtained from CT at the level of L1–2 intervertebral disc space, and the VAT/SAT, VAT/TAT ratios were calculated. The postoperative parameter changes in both groups were evaluated compared to the preoperative values. The level of statistical significance was considered as p<0.05.Results The time interval between preoperative and postoperative CT measurements were 10.37 months (6–17) in CS and 9.75 months (7–15) in NFA groups (p=073). Preoperative CT indicated that the patients with CS had larger VAT and TAT areas (p=0.03, p=0.02) but SAT remained unchanged (p=0.08). However, postoperative CT revealed that there was no difference between the two groups in terms of VAT, TAT, and SAT areas (p=0.87, p=0.36, p=0.14). Postoperatively, in patients with CS, there was a decrease in VAT and TAT areas (p=0.01 for both) and VAT/SAT and VAT/TAT ratios (p=0.03, p=0.02) but SAT remained unchanged (p=0.10). In patients with NFA, no change was detected in the postoperative SAT, TAT, and VAT areas (p=0.12, p=0.40, p=0.99) or the VAT/SAT and VAT/TAT ratios (p=0.38, p=0.62).Conclusions Adrenalectomy is an effective treatment method leading to a decrease in the VAT, TAT areas, and VAT/SAT and VAT/TAT ratios in patients with cortisol producing adrenocortical adenoma. Thus, CT facilitates quantitative demonstration of the changes while evaluating the response of these patients to treatment.
Keywords: Adrenal adenoma; Cushing’s syndrome; computed tomography; VAT; SAT; TAT